Evaluasi Rekam Medis Elektronik dengan Metode HOT-fit di Klinik Saraf RS Mitra Plumbon - Franki Franki; Irda Sari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Electronic medical records are listed in Permenkes number 269/MENKES/PER/III/2008 in article 2 which contains "(1) Medical records must be made in writing, complete, and clear or electronically (2) The administration of medical records using electronic information technology is regulated further with its own regulations. To find out the problems of electronic medical records at the neuro clinic at Mitra Plumbon Hospital, an evaluation was carried out using the Human, Organization, Technology and Net Benefit (HOT fit Model) method. The type of research was descriptive qualitative. All officers involved in the information system as research subjects, (3 main informants and 2 triangulation informants) Collecting data through in-depth interviews using interview guidelines. Processing and analyzing data using a content analysis approach. high school patient registration officer, users can receive the EMR system, the management organization is very supportive, there is no team, operational guidelines, technical guidelines, EMR SOPs, unstable internet technology, duplicate prescriptions, drug prescriptions are difficult to find, can't see before EMR, patients who register online is often late. Keywords: evaluation; RME; HOT fit ABSTRAK Rekam medis elektronik tercantum dalam Permenkes nomor 269/MENKES/PER/III/2008 pada pasal 2 yang berisi “(1) Rekam medis harus dibuat secara tertulis, lengkap, dan jelas atau secara elektronik (2) Penyelenggaraan rekam medis menggunakan teknologi informasi elektronik diatur lebih lanjut dengan peraturan sendiri. Untuk mengetahui permasalahan rekam medis elektronik di klinik saraf rumah sakit Mitra Plumbon dilakukan evaluasi dengan metode Human, Organization, Technology dan Net Benefit (HOT fit Model).Jenis Penelitian adalah deskriptif kualitatif. Semua petugas yang terlibat dalam sistem Informasi tersebut sebagai subyek penelitian, (informan Utama sebanyak 3 orang dan informan triangulasi sebanyak 2 orang) Pengumpulan data melalui wawancara mendalam menggunakan pedoman wawancara. Pengolahan dan analisis data menggunakan pendekatan analisis isi (content analysis).Human pedaftaran pasien pendidikan SMA, pengguna dapat menerima sistem EMR, Organization manajemen sangat mendukung, belum ada tim, juklak, juknis, SOP EMR, Technology internet yang tidak stabil, sering terjadi gangguan saat duplikasi resep, resep obat sulit dicari, tidak bisa melihat sebelum EMR, pasien yang daftar online sering terlambat. Kata kunci: evaluasi; RME; HOT fit